Movimento das ocupações escolares: “o fazer político dos jovens secundaristas” no município de Francisco Beltrão-PR - David, Franciele Maria (2019)
In 2016, in the state of Parana, Brazil, in response to Provisional Measure n. 746 proposing reforming secondary schools’ system in the country, high school students went to occupy campi. Around 850 buildings were occupied in Parana only. This occupation process reached other states and universities. School occupations in Francisco Beltrao city is our study object. This qualitative research aims to analyze the state school occupation process that occurred in 2016, in particular in the city of Francisco Beltrao, so that to reveal to what extent exactly high school students’ participation in this movement has contributed to their political training. Our specific objectives are as following: analyze to what extent school occupation experiences became a political act of working-class youth, producing a self-training process; historicize students’ occupation process in Francisco Beltrao; study the main features in students’ organization and how their relationship with traditional students’ organizations happens. Thus, our study used Marxist historian E.P. Thompson’s category of experience to ascertain the training potential of the occupations. In addition to bibliographic research and an analysis over publications produced by newspapers and websites during and after the Occupy movements, we conducted 11 semi-structured interviews with young participants of occupations in Francisco Beltrao. Our account considers initially the historical and social context of these students’ occupation, a context marked by neoliberal educational policies, especially from the 90s on. Then, aiming to analyze these occupation processes in Brazil, based on Martins (2009) basically, we defined occupation as an analysis category, and see school occupations in their relationship to other occupation movements in the history of student movements. In this way, we considered some examples of movements where occupations became fighting strategies to deepen, as a consequence, students’ occupations especially in 2015 and 2016, highlighting their main features. Finally, we have analyzed students’ experience at school occupations in Francisco Beltrao, in Parana, bringing up their journey in the city: occupied schools, youngsters’ organizational forms, life in the movement, learning, tensions, and conflicts. We have also highlighted the making of these high school students, in a training process where political, social, cultural, and pedagogical dimensions are articulated and constitute important respect for a political formation of them. In such occupations, we have brought about their self-organizational format, tests of an extended democracy, and the tension of current school form. The students participating in the study have lived other collective viewpoints, enabling a breakthrough in the current organizational format, making counter-hegemonic models of experience possible. It has also become a milestone for the reorganization of the students’ movement in the city.